Strong-cohesiveness diaphragm, preparation method and application in lithium ion battery

A strong adhesive diaphragm with a polymer slurry is used to bond lithium-ion battery components at lower temperatures, enhancing adhesion and safety, and improving production efficiency by using polyethylene and specific polymer coatings.

CN119208918APending Publication Date: 2024-12-27JIANGSU BEIXING NEW MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411316148.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing lithium-ion battery manufacturing processes require high-temperature hot-pressing to bond the diaphragm with electrodes, leading to reduced production efficiency, increased energy consumption, brittle cracking, and insufficient adhesion, which can cause internal short circuits and bulging.

Method used

A strong adhesive diaphragm composed of a polyethylene membrane and a polymer slurry containing specific components like polyethyl acrylate, polysulfate-ethyl acrylate copolymer, or polyvinylidene fluoride-ethyl acrylate copolymer, is coated on the diaphragm and bonded with electrodes at lower temperatures using a simple coating process and hot pressing, enhancing adhesion and avoiding brittle cracking.

Benefits of technology

Improves production efficiency, adhesive performance, and safety by maintaining diaphragm integrity, preventing peeling, and reducing internal short circuits, while maintaining air permeability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208918A_ABST
    Figure CN119208918A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a high-cohesiveness diaphragm, a preparation method and application of the high-cohesiveness diaphragm in a lithium ion battery. Comprising a polyethylene diaphragm and high-cohesiveness polymer slurry, the high-cohesiveness polymer slurry comprises high-cohesiveness polymer particles, a dispersing agent, a wetting agent, a binding agent and a thickening agent, the high-cohesiveness polymer with low crystallinity and low glass transition temperature is adopted, and the production efficiency of a battery cell is improved; meanwhile, the specific high-cohesiveness polymer slurry is used, so that the cohesiveness of the high-cohesiveness polymer is improved, and the coating efficiency on the diaphragm is also improved; a specific coating process is adopted, so that the process is simple and easy to implement, and the production efficiency is improved; through a specific hot pressing process, the bonding strength is improved, the diaphragm material is prevented from brittle rupture, the cycle performance and the safety of the battery are also improved, in addition, proper strong bonding material coating thickness and surface density are selected, the good bonding property is also realized, and the air permeability of the diaphragm is not obviously influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a strong adhesive diaphragm, a preparation method and application in lithium ion batteries. Background Art

[0002] Lithium-ion batteries have become an indispensable source of energy for mobile electronic devices, electric vehicles and energy storage systems due to their high energy density, long life and no memory effect. The performance of lithium-ion batteries is closely related to the diaphragm material inside them. As the isolation layer between the positive and negative electrodes of lithium-ion batteries, the diaphragm not only isolates the positive and negative electrodes to prevent short circuits, but also ensures the smooth transmission of lithium ions. The performance of the diaphragm material directly affects the interface structure, internal resistance, capacity, cycle and safety performance of lithium-ion batteries. In the manufacturing process of lithium-ion batteries, the adhesion between the diaphragm and the positive and negative electrode materials is a key factor. Good adhesion can ensure that during the battery charging and discharging process, the diaphragm and the positive and negative electrode materials will not be relatively displaced, thereby avoiding problems such as internal short circuits and bulging of the battery.

[0003] At present, the main method to improve the adhesion between the diaphragm and the positive and negative electrode materials is to coat the adhesive material on the surface of the diaphragm; the existing solution mainly uses adhesive materials such as polyvinylidene fluoride and polymethyl methacrylate to coat the surface of the diaphragm, and then softens the adhesive material or reaches the glass transition temperature through high-temperature hot pressing, thereby enhancing the adhesion between the diaphragm and the electrode; this method can effectively improve the adhesion between the diaphragm and the positive and negative electrode materials, thereby improving the performance and safety of the battery.

[0004] However, there are some problems with the existing technology. First, the softening point of PVDF materials is around 90°C, and the glass transition temperature of PMMA materials is around 104°C, which means that after winding, the battery cell needs to be hot-pressed at high temperature for a long time to allow the diaphragm to bond with the electrode, which leads to reduced battery cell production efficiency and increased energy consumption. Second, the high-temperature hot-pressing process can easily lead to brittle cracking of the diaphragm material, thereby affecting the cycle performance and safety of the battery. In addition, existing adhesive materials generally have the problem of insufficient adhesion, and are prone to peeling during the battery charging and discharging process, resulting in internal short circuits and bulging of the battery. Summary of the invention

[0005] The purpose of the present invention is to provide a strong adhesive diaphragm, a preparation method and application in lithium-ion batteries, aiming to solve some problems existing in the prior art; first, the softening point of PVDF materials is about 90°C, and the glass transition temperature of PMMA materials is about 104°C, which means that after winding, the battery cell needs to be hot-pressed at high temperature for a long time to make the diaphragm and the electrode sheet bonded, which leads to a decrease in the production efficiency of the battery cell and an increase in energy consumption; secondly, the high-temperature hot-pressing process is prone to brittle cracking of the diaphragm material, thereby affecting the cycle performance and safety of the battery; in addition, the existing adhesive materials generally have the problem of insufficient adhesion, and peeling is prone to occur during the battery charging and discharging process, thereby leading to technical problems such as internal short circuit and bulging of the battery.

[0006] To achieve the above object, the present invention adopts a strong bonding membrane, which includes a polyethylene membrane and a strong bonding polymer slurry, wherein the strong bonding polymer slurry includes strong bonding polymer particles, a dispersant, a wetting agent, a binder and a thickener.

[0007] Among them, the dispersant is one of modified ammonium salt copolymer and polycarboxylate, the wetting agent is one of modified water-based alkyl alcohol amide, non-ionic multi-branched alcohol modified surfactant and fatty alcohol polyether, the binder is acrylate copolymer, and the thickener is sodium carboxymethyl cellulose.

[0008] The mass fraction of the dispersant is 0.1wt% to 0.3wt%, the mass fraction of the wetting agent is 0.1wt% to 0.2wt%, the mass fraction of the binder is 4wt% to 5wt%, and the mass fraction of the thickener is 2wt%.

[0009] Wherein, the mass fraction of the strong adhesive polymer particles is 10wt%.

[0010] Wherein, the strong adhesive polymer particles are one of polyethyl acrylate, polysulfate-ethyl acrylate copolymer or polyvinylidene fluoride-ethyl acrylate copolymer.

[0011] The present invention also provides a method for preparing a strong adhesive diaphragm, which is applied to the above-mentioned strong adhesive diaphragm, comprising the following steps:

[0012] S1: Select the strong adhesive polymer particles, and add a dispersant, a wetting agent, a binder and a thickener in sequence;

[0013] S2: using a ball mill to uniformly mix the strongly adhesive polymer particles, the dispersant, the wetting agent, the adhesive and the thickener to obtain a strongly adhesive polymer slurry;

[0014] S3: Select the polyethylene separator with a thickness of 9 μm, place it on a coating machine, and simultaneously coat the strong adhesive polymer slurry on one side of the polyethylene separator by a spraying process;

[0015] S4: placing the strong adhesive polymer particles coated with the strong adhesive polymer slurry and the lithium iron phosphate material pole piece on a hot press for hot pressing to complete the preparation.

[0016] Wherein, the viscosity of the strong adhesive polymer slurry is 120cp-150cp.

[0017] The coating thickness of the spraying process is 2 microns and the surface density is 0.8 g / m 2 ~1.0g / m 2 .

[0018] The hot pressing temperature of the hot pressing machine is 40° C. to 90° C., the hot pressing pressure is 500 MPa, and the hot pressing time is 0.5 minute to 1 minute.

[0019] Among them, the strong adhesive diaphragm is used in lithium ion batteries.

[0020] The invention discloses a strong adhesive diaphragm, a preparation method and an application thereof in a lithium ion battery, comprising a polyethylene diaphragm and a strong adhesive polymer slurry, wherein the strong adhesive polymer slurry comprises strong adhesive polymer particles, a dispersant, a wetting agent, a binder and a thickener, and improves the production efficiency of the battery core by adopting a strong adhesive polymer with low crystallinity and low glass transition temperature; at the same time, the use of the strong adhesive polymer slurry with a specific composition can not only improve the adhesive performance of the strong adhesive polymer, but also improve its coating efficiency on the diaphragm; and a specific coating process is adopted to make the process simple and easy, thereby improving the production efficiency; finally, through a specific hot pressing process, not only the bonding strength can be improved, but also the embrittlement of the diaphragm material can be avoided, thereby improving the cycle performance and safety of the battery, and in addition, an appropriate thickness and surface density of the strong adhesive material coating are selected, and the strong adhesive material coating not only has good adhesive performance, but also does not significantly affect the air permeability of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 is a flowchart of the steps of the first embodiment of the present invention. DETAILED DESCRIPTION

[0023] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0024] The invention provides a strong-adhesive diaphragm, comprising a polyethylene diaphragm and a strong-adhesive polymer slurry, wherein the strong-adhesive polymer slurry comprises strong-adhesive polymer particles, a dispersant, a wetting agent, a binder and a thickener.

[0025] Furthermore, the dispersant is one of modified ammonium salt copolymer and polycarboxylate, the wetting agent is one of modified water-based alkyl alcohol amide, nonionic multi-branched alcohol modified surfactant and fatty alcohol polyether, the binder is acrylate copolymer, and the thickener is sodium carboxymethyl cellulose.

[0026] Furthermore, the mass fraction of the dispersant is 0.1wt% to 0.3wt%, the mass fraction of the wetting agent is 0.1wt% to 0.2wt%, the mass fraction of the binder is 4wt% to 5wt%, and the mass fraction of the thickener is 2wt%.

[0027] Furthermore, the mass fraction of the strong adhesive polymer particles is 10wt%.

[0028] Furthermore, the strong adhesive polymer particles are one of polyethyl acrylate, polysulfate-ethyl acrylate copolymer or polyvinylidene fluoride-ethyl acrylate copolymer.

[0029] For further information, see Figure 1 The present invention also provides a method for preparing a strong adhesive diaphragm, which is applied to the above-mentioned strong adhesive diaphragm, comprising the following steps:

[0030] S1: Select the strong adhesive polymer particles, and add a dispersant, a wetting agent, a binder and a thickener in sequence;

[0031] S2: using a ball mill to uniformly mix the strongly adhesive polymer particles, the dispersant, the wetting agent, the adhesive and the thickener to obtain a strongly adhesive polymer slurry;

[0032] S3: Select the polyethylene separator with a thickness of 9 μm, place it on a coating machine, and simultaneously coat the strong adhesive polymer slurry on one side of the polyethylene separator by a spraying process;

[0033] S4: placing the strong adhesive polymer particles coated with the strong adhesive polymer slurry and the lithium iron phosphate material pole piece on a hot press for hot pressing to complete the preparation.

[0034] Furthermore, the viscosity of the strong adhesive polymer slurry is 120cp-150cp.

[0035] Furthermore, the coating thickness of the spraying process is 2 microns and the surface density is 0.8 g / m 2 ~1.0g / m 2 .

[0036] Furthermore, the hot pressing temperature of the hot pressing machine is 40° C. to 90° C., the hot pressing pressure is 500 MPa, and the hot pressing time is 0.5 minute to 1 minute.

[0037] Furthermore, the strong adhesive diaphragm is used in lithium-ion batteries.

[0038] In this embodiment, the production efficiency of the battery cell is improved by adopting a strong adhesive polymer with low crystallinity and low glass transition temperature; at the same time, the use of the strong adhesive polymer slurry with a specific composition can not only improve the adhesive properties of the strong adhesive polymer, but also improve its coating efficiency on the diaphragm; and a specific coating process is adopted to make the process simple and easy, which can improve the production efficiency; finally, through a specific hot pressing process, not only the bonding strength can be improved, but also the brittle cracking of the diaphragm material can be avoided, thereby improving the cycle performance and safety of the battery. In addition, by selecting an appropriate strong adhesive material coating thickness and surface density, this strong adhesive material coating not only has good bonding properties, but also will not significantly affect the air permeability of the diaphragm.

[0039] First embodiment:

[0040] In this embodiment, step one: select polyethyl acrylate as the strong bonding polymer particles, with a mass fraction of 10wt%; then, add a dispersant with a mass fraction of 0.3wt%; then, add a wetting agent with a mass fraction of 0.1wt%; then, add a binder with a mass fraction of 4wt%; finally, add a thickener with a mass fraction of 2wt%; the rest is deionized water, so that the total mass fraction reaches 100wt%; use a ball mill to mix all the materials evenly to obtain the strong bonding polymer slurry with a viscosity of 150cp; step two: select the polyethylene diaphragm with a thickness of 9 microns and place it on a coater; apply the strong bonding polymer slurry prepared in step one on one side of the polyethylene diaphragm by a spraying process, the coating thickness is 2 microns, and the surface density is 1.0g / m 2; Step 3: Place the polyethylene diaphragm coated with the strong adhesive polymer slurry and the lithium iron phosphate material pole piece on a hot press; set the hot pressing temperature to 40°C, the hot pressing pressure to 500MPa, and the hot pressing time to 1 minute; after hot pressing, the bonding strength between the strong adhesive diaphragm and the lithium iron phosphate material pole piece is 38N / m; Through the above steps, a strong adhesive diaphragm can be obtained, and the thickness of the strong adhesive material coating is 2 microns and the surface density is 1.0g / m 2 , the coating permeability increment is 15s / 100cc; this strong bonding diaphragm has good bonding properties and will not significantly affect the permeability of the diaphragm, thereby improving the cycle performance and safety of lithium-ion batteries; at the same time, due to the use of hot pressing process at a lower temperature, the brittle cracking of the diaphragm material is avoided and the battery cell production efficiency is improved.

[0041] Second embodiment:

[0042] In this embodiment, step one: select polysulfate-ethyl acrylate copolymer as the strong adhesive polymer particles, with a mass fraction of 10wt%; then, add a dispersant with a mass fraction of 0.3wt%; then, add a wetting agent with a mass fraction of 0.1wt%; then, add a binder with a mass fraction of 4wt%; finally, add a thickener with a mass fraction of 2wt%; the rest is deionized water, so that the total mass fraction reaches 100wt%; use a ball mill to mix all the materials evenly to obtain a strong adhesive polymer slurry with a viscosity of 150cp; step two: select the polyethylene diaphragm with a thickness of 9 microns and place it on a coater; apply the strong adhesive polymer slurry prepared in step one on one side of the polyethylene diaphragm by a spraying process, the coating thickness is 2 microns, and the surface density is 0.8g / m 2 ; Step 3: Place the polyethylene diaphragm coated with the strong adhesive polymer slurry and the lithium iron phosphate material pole piece on a hot press; set the hot pressing temperature to 40°C, the hot pressing pressure to 500MPa, and the hot pressing time to 1 minute; after hot pressing, the bonding strength between the strong adhesive diaphragm and the lithium iron phosphate material pole piece is 26N / m; Through the above steps, a strong adhesive diaphragm can be obtained, and the thickness of the strong adhesive material coating is 2 microns and the surface density is 1.0g / m 2 , the coating permeability increment is 5s / 100cc.

[0043] Third embodiment:

[0044] In this embodiment, step one: select polyvinylidene fluoride-ethyl acrylate as the strong bonding polymer particles, with a mass fraction of 10wt%; then, add a dispersant with a mass fraction of 0.1wt%; then, add a wetting agent with a mass fraction of 0.2wt%; then, add a binder with a mass fraction of 5wt%; finally, add a thickener with a mass fraction of 2wt%; the rest is deionized water, so that the total mass fraction reaches 100wt%; use a ball mill to mix all the materials evenly to obtain the strong bonding polymer slurry with a viscosity of 150cp; step two: select the polyethylene diaphragm with a thickness of 9 microns and place it on a coater; apply the strong bonding polymer slurry prepared in step one on one side of the polyethylene diaphragm by a spraying process, the coating thickness is 2 microns, and the surface density is 0.8g / m 2 ; Step 3: Place the polyethylene diaphragm coated with the strong adhesive polymer slurry and the lithium iron phosphate material pole piece on a hot press; set the hot pressing temperature to 40°C, the hot pressing pressure to 500MPa, and the hot pressing time to 1 minute; after hot pressing, the bonding strength between the strong adhesive diaphragm and the lithium iron phosphate material pole piece is 30N / m; Through the above steps, a strong adhesive diaphragm can be obtained, and the thickness of the strong adhesive material coating is 2 microns and the surface density is 1.0g / m 2 , the coating permeability increment is 5s / 100cc.

[0045] The present invention also provides two groups of comparative examples, as follows:

[0046] Comparative Example 1:

[0047] First, polyvinylidene fluoride is selected as the strong bonding polymer particles, and its mass fraction is 10wt%; then, a dispersant is added, and its mass fraction is 0.3wt%; then, a wetting agent is added, and its mass fraction is 0.1wt%; subsequently, a binder is added, and its mass fraction is 4wt%; finally, a thickener is added, and its mass fraction is 2wt%; the rest is deionized water, so that the total mass fraction reaches 100wt%; all materials are mixed evenly using a ball mill to obtain the strong bonding polymer slurry with a viscosity of 130cp; Step 2: Select the polyethylene diaphragm with a thickness of 9 microns and place it on a coating machine; The strong bonding polymer slurry prepared in step 1 is coated on one side of the polyethylene diaphragm by a spraying process, and the coating thickness is 2 microns and the surface density is 0.8g / m 2; Step 3: Place the polyethylene diaphragm coated with the strong adhesive polymer slurry and the lithium iron phosphate material pole piece on a hot press; set the hot pressing temperature to 90°C, the hot pressing pressure to 500MPa, and the hot pressing time to 1 minute; after hot pressing, the bonding strength between the strong adhesive diaphragm and the lithium iron phosphate material pole piece is 1N / m; Through the above steps, a strong adhesive diaphragm can be obtained, and the thickness of the strong adhesive material coating is 2 microns and the surface density is 1.0g / m 2 , the coating permeability increment is 25s / 100cc.

[0048] Comparative Example 2:

[0049] First, polymethyl methacrylate is selected as the strong adhesive polymer particles, and its mass fraction is 10wt%; then, a dispersant is added, and its mass fraction is 0.3wt%; then, a wetting agent is added, and its mass fraction is 0.1wt%; subsequently, a binder is added, and its mass fraction is 4wt%; finally, a thickener is added, and its mass fraction is 2wt%; the rest is deionized water, so that the total mass fraction reaches 100wt%; all materials are mixed evenly using a ball mill to obtain a strong adhesive polymer slurry with a viscosity of 120cp; Step 2: Select the polyethylene diaphragm with a thickness of 9 microns and place it on a coating machine; The strong adhesive polymer slurry prepared in step 1 is applied to one side of the polyethylene diaphragm by a spraying process, and the coating thickness is 2 microns and the surface density is 0.8g / m 2 ; Step 3: Place the polyethylene diaphragm coated with the strong adhesive polymer slurry and the lithium iron phosphate material pole piece on a hot press; set the hot pressing temperature to 90°C, the hot pressing pressure to 500MPa, and the hot pressing time to 1 minute; after hot pressing, the bonding strength between the strong adhesive diaphragm and the lithium iron phosphate material pole piece is 3N / m; Through the above steps, a strong adhesive diaphragm can be obtained, and the thickness of the strong adhesive material coating is 2 microns and the surface density is 1.0g / m 2 , the coating permeability increment is 20s / 100cc.

[0050] In the present invention, a strong adhesive polymer slurry is applied to one or both sides of a conventional commercial lithium-ion battery separator to form a strong adhesive material coating, and a strong adhesive effect can be formed between the separator and the pole piece by hot pressing at a relatively low temperature; this greatly reduces the temperature and time of battery cell production, improves the efficiency of battery cell production, and saves energy; secondly, the strong adhesive polymer of the present invention has a glass transition temperature of ≤30°C, a crystallinity of 20%≤≤35%, and a viscosity-average molecular weight of ≥100kDa; this material has excellent adhesive properties, can effectively prevent peeling during battery charging and discharging, and avoid problems such as internal short circuits and bulging in the battery, thereby improving the cycle performance and safety of the battery; and the strong adhesive polymer of the present invention can be polyethyl acrylate, polysulfate-ethyl acrylate copolymer, polyvinylidene fluoride-ethyl acrylate copolymer materials; this variety The material selection provides the possibility for preparing strong adhesion membranes with different performance requirements and meets the needs of different application scenarios; at the same time, the strong adhesion polymer slurry of the present invention includes strong adhesion polymer particles, dispersant, wetting agent, binder, thickener, and the rest is deionized water; these materials are all environmentally friendly materials, non-toxic and harmless, will not pollute the environment, and are in line with the development trend of green environmental protection; finally, the coating process of the strong adhesion polymer slurry of the present invention is one of spraying and spot coating; this simple and easy coating process does not require complex equipment and technical support, and is easy to promote and apply; in summary, compared with the prior art, the present invention has the advantages of high production efficiency, excellent adhesion performance, wide material selection, environmental protection and pollution-free, simple coating process, etc., and is a preparation technology for lithium ion battery strong adhesion membranes with broad application prospects.

[0051] In the present invention, by utilizing the low crystallinity and low glass transition temperature characteristics of the strong bonding material, a strong bonding effect can be formed between the diaphragm and the pole piece by hot pressing at a relatively low temperature, thereby improving the production efficiency of the battery cell; the strong bonding polymer slurry in the present design can be coated on one or both sides of a conventional commercial lithium-ion battery diaphragm by a process of spraying or spot coating, thereby forming a strong bonding material coating; this coating process is simple and easy to implement, and can improve production efficiency, while using a specific hot pressing process: the strong bonding diaphragm and the lithium iron phosphate material pole piece in the present design are hot pressed at a temperature of 30 to 50°C, a hot pressing pressure of 500MPa, and a hot pressing time of 0.5 minutes to form a bonding strength of ≥10N / m; this hot pressing process can not only improve the bonding strength, but also avoid the embrittlement of the diaphragm material, thereby improving the cycle performance and safety of the battery; and, select an appropriate strong bonding material coating thickness and surface density: the strong bonding material coating thickness in the present design is 0.5 to 5 microns, and the surface density is 0.2 to 2.0g / m 2 , the coating air permeability increment is 10 to 20s / 100; this strong bonding material coating not only has good bonding properties, but also does not significantly affect the air permeability of the diaphragm.

[0052] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A strong adhesive diaphragm, characterized in that: The invention comprises a polyethylene diaphragm and a strong adhesive polymer slurry, wherein the strong adhesive polymer slurry comprises strong adhesive polymer particles, a dispersant, a wetting agent, a binder and a thickener.

2. The strong adhesive diaphragm according to claim 1, characterized in that: The dispersant is one of modified ammonium salt copolymer and polycarboxylate, the wetting agent is one of modified water-based alkyl alcohol amide, nonionic multi-branched alcohol modified surfactant and fatty alcohol polyether, the binder is acrylate copolymer, and the thickener is sodium carboxymethyl cellulose.

3. The strong adhesive diaphragm according to claim 2, characterized in that: The mass fraction of the dispersant is 0.1wt% to 0.3wt%, the mass fraction of the wetting agent is 0.1wt% to 0.2wt%, the mass fraction of the binder is 4wt% to 5wt%, and the mass fraction of the thickener is 2wt%.

4. The strong adhesive diaphragm according to claim 3, characterized in that: The mass fraction of the strong bonding polymer particles is 10 wt %.

5. The strong adhesive diaphragm according to claim 4, characterized in that: The strong adhesive polymer particles are selected from one of polyethyl acrylate, polysulfate-ethyl acrylate copolymer or polyvinylidene fluoride-ethyl acrylate copolymer.

6. A method for preparing a strong adhesive diaphragm, applied to the strong adhesive diaphragm as claimed in claim 5, characterized in that: The following steps are involved: S1: Select the strong adhesive polymer particles, and add a dispersant, a wetting agent, a binder and a thickener in sequence; S2: using a ball mill to evenly mix the strongly adhesive polymer particles, the dispersant, the wetting agent, the adhesive and the thickener to obtain a strongly adhesive polymer slurry; S3: Select the polyethylene separator with a thickness of 9 μm, place it on a coating machine, and simultaneously coat the strong adhesive polymer slurry on one side of the polyethylene separator by a spraying process; S4: placing the strong adhesive polymer particles coated with the strong adhesive polymer slurry and the lithium iron phosphate material pole piece on a hot press for hot pressing to complete the preparation.

7. A method for preparing a strong adhesive diaphragm according to claim 6, characterized in that: The viscosity of the strong adhesive polymer slurry is 120cp-150cp.

8. A method for preparing a strong adhesive diaphragm according to claim 6, characterized in that: The coating thickness of the spraying process is 2 microns and the surface density is 0.8g / m 2 ~1.0g / m 2 .

9. A method for preparing a strong adhesive diaphragm according to claim 6, characterized in that: The hot pressing temperature of the hot pressing machine is 40° C. to 90° C., the hot pressing pressure is 500 MPa, and the hot pressing time is 0.5 minute to 1 minute.

10. Use of the strong adhesive separator according to any one of claims 1 to 5 in lithium ion batteries.